Rational synthesis of 1,3,4-thiadiazole based ESIPT-fluorescent probe for detection of Cu2+ and H2S in herbs, wine and fruits - Sun, Yu; Mu, Jie; Wang, Yongchen; Lü, Chengwei; Zou, Li-Wei (Analytica chimica acta, 2024)
Here, 1,3,4-thiadiazole unit was employed as novel excited state intramolecular proton transfer (ESIPT) structure to prepare favorable fluorescent probe. High selectivity and rapid response to Cu2+ was obtained and the settling reaction was also used to recover ESIPT characteristics of probe to achieve sequential detection of H2S. Remarkable color change of solution from colorless to bright yellow and fluorescence emission from green to dark realized the visual detection of Cu2+ by naked eyes and transition of probe into portable fluorescent test strips. As expected, L-E could be utilized to quantitatively sense Cu2+ and H2S in different actual water and food samples including herbs, wine and fruits. The limits of detection for Cu2+ and H2S were as low as 34.5 nM and 38.6 nM. Also, probe L-E achieved real-time, portable, on-site quantitative detection of Cu2+ via a colorimeter and a smartphone platform with limit of detection to 90.3 nM. [Display omitted] •1,3,4-thiadiazole-based fluorescent probe with ESIPT effect was synthesized.•L-E can relay identify Cu2+ and H2S with good sensitivity, selectivity and LOD value.•L-E was suitable to assay the Cu2+ and H2S level in herbs, wine and fruits.•A color signal-based visual assessment was developed using smartphone platform.